IL-12, IL-6 and IFN-γ production by lymphocytes of pregnant women with rheumatoid arthritis remission during pregnancy - Henryk Tchórzewski; Grzegorz Krasomski; Lidia Biesiada; Ewa Glowacka; Malgorzata Banasik; Przemyslaw Lewkowicz (Mediators of Inflammation)
Background: Rheumatoid arthritis (RA) is an autoimmune disease with progressive activity. The RA remission was observed in women during pregnancy, but the mechanism responsible for remission is hypothetical only and concerns mechanisms of immune regulation such as lymphocyte subpopulations and interleukin production.